Numerical Study of Vortex Shedding Control Using Viscoelastic Flow Over an Elliptical Cylinder - Annisa Dwi Sulistyaningtyas; Basuki Widodo; Chairul Imron; Hanim Faizah ((IJCSAM) International Journal of Computing Science and Applied Mathematics, 2026)
Vortex-Induced Vibration (VIV) mitigation is a critical issue in engineering systems involving bluff bodies subjected to fluid flow. This study presents a numerical investigation of viscoelastic fluid flow over an elliptical cylinder as a passive control strategy to suppress vortex shedding. The governing continuity, momentum, and energy equations for an incompressible viscoelastic fluid are formulated and solved using an implicit finite difference method. The viscoelastic behavior of the fluid is incorporated through a nonlinear constitutive model, and the resulting system of equations is transformed into a dimensionless form to facilitate analysis. The study focuses on the effects of key parameters, including the viscoelastic parameter K, the Prandtl number P r, and the geometric aspect ratio a/b of the elliptical cylinder. Numerical simulations are performed using MATLAB to evaluate the resulting velocity and temperature distributions within the boundary layer region. The results indicate that increasing the viscoelastic parameter significantly reduces the peak velocity near the wall and weakens the velocity gradient, leading to a decrease in shear stress. In addition, higher viscoelasticity contributes to a thicker momentum and thermal boundary layer, which reduces the rate of heat transfer from the surface. Furthermore, variations in the Prandtl number and aspect ratio are found to influence the localization of thermal and momentum transport. Higher values of P r result in thinner thermal boundary layers and enhanced temperature gradients near the surface, while changes in a/b primarily affect the near-wall flow structure. Overall, the combined effects of viscoelasticity and geometric modification demonstrate a strong potential for attenuating vortex shedding and reducing the likelihood and intensity of VIV. These findings provide valuable insights for the design of engineering systems involving non-Newtonian fluids and flow-induced vibrations.